Recycling batteries. - McMichael, F.C.
Hundreds of millions of large and billions of small batteries are used up annually in the service of all manner of electronic devices. Until recently, the tons of toxic materials in these batteries would wind up in the garbage, but the systematic collection and recycling of spent batteries is growing. Effective recycling involves changes at all stages of battery life, starting with production. Manufacturers should attempt to use recycled materials themselves, label batteries clearly for easier sorting, and ensure that batteries can be effectively recycled. Consumers need to take part in recycling programs by separating batteries from other wastes-doing so after their disposal in general municipal solid wastes is quite expensive per ton of battery material recovered. Retailers and shippers are needed to collect and return post-consumer batteries to recyclers. Finally, recycling plants and processes are needed for each of the various battery types and materials. The authors discuss materials management, battery design issues, systematic collection, recycling technologies, nickel and cadmium recovery, consumer cell recycling, detoxification costs, and future prospects
Keywords: Battery design; Battery labeling; Cadmium recovery; Consumer cell recycling; Detoxification costs; Materials management; Nickel recovery; Recycling plants; Recycling programs; Recycling technologies; Spent batteries recycling; Toxic materials